2001
DOI: 10.1038/sj.cgt.7700306
|View full text |Cite
|
Sign up to set email alerts
|

A herpes simplex virus type 1 mutant deleted for γ34.5 and LAT kills glioma cells in vitro and is inhibited for in vivo reactivation

Abstract: To create an oncolytic herpes simplex virus type 1 ( HSV -1 ) that is inhibited for reactivation, we constructed a novel herpes recombinant virus with deletions in the 34.5 and LAT genes. The LAT gene was replaced by the gene for green fluorescent protein, thereby allowing viral infection to be followed. This virus, designated DM33, is effective in killing primary and established human glioma cell lines in culture. DM33 is considerably less virulent following intracerebral inoculation of HSV -susceptible BALB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…1B), and a LAT-␥34.5-null mutant expressing IL-4 (vIL-4) (45). Ocular challenge of mice with these recombinant viruses showed that, similar to the parental virus (49) and other recombinant HSV-1 lacking the ␥34.5 gene (8), these recombinant viruses are also attenuated (46). CL7 and spleen cells were grown in RPMI 1640 supplemented with 10% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1B), and a LAT-␥34.5-null mutant expressing IL-4 (vIL-4) (45). Ocular challenge of mice with these recombinant viruses showed that, similar to the parental virus (49) and other recombinant HSV-1 lacking the ␥34.5 gene (8), these recombinant viruses are also attenuated (46). CL7 and spleen cells were grown in RPMI 1640 supplemented with 10% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, pLAT-IL12p35 or pLAT-IL12p40 were cotransfected individually with infectious HSV-1 double mutant (LAT-␥34.5-null mutant) DNA by using the calcium phosphate method. This virus is a mutant of HSV-1 strain McKrae in which 1.8 kb of LAT and 0.9 kb of ␥34.5 have been deleted (49). Viruses from the cotransfection were plated, and the isolated plaques were picked and then screened for insertion of IL-12p35 or IL-12p40 gene by using restriction digestion and Southern blot analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, pLAT-IL-2, pLAT-IL-4, or pLAT-IFN␥ was cotransfected with infectious HSV-1 double mutant (DM-33) DNA by the calcium phosphate method. The DM-33 (LAT-␥34.5-null mutant) virus is a mutant of HSV-1 strain McKrae in which 1.8 kb of LAT and 0.9 kb of ␥34.5 have been deleted (42). Viruses from the cotransfection were plated, and the isolated plaques were picked and then screened for the presence of the IL-2, IL-4, or IFN-␥ gene using restriction digestion and Southern blot analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, DM33 demonstrated dose-dependent antitumor activity in glioma cell lines. The safety of DM33 was supported by its attenuated toxicity against neuronal cells, astrocytes, and endothelial cells [26]. Based on its efficacy and safety, DM33 shows considerable promise as an oncolytic virus for cancer treatment.…”
Section: An Overview Of Hsvmentioning
confidence: 99%